2016
DOI: 10.1002/ange.201511341
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake and Assembly of Alkanes within a Porous Nanocapsule in Water: New Information about Hydrophobic Confinement

Abstract: In Nature,e nzymes provide hydrophobic cavities and channelsf or sequestering small alkanes or long-chain alkylg roups from water.S imilarly,t he porous metal oxide capsule [{Mo VI 6 O 21 (H 2 O) 6 } 12 {(Mo V 2 O 4 ) 30 (L) 29 (H 2 O) 2 }] 41À (L = propionate ligand) features distinct domains for sequestering differently sized alkanes (as in Nature) as well as internal dimensions suitable for multi-alkane clustering.The ethyl tails of the 29 endohedrally coordinated ligands,L,form aspherical, hydrophobic "she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The Keplerate-type POMs belong to this class of compounds and correspond probably to one of the most fascinating and aesthetic arrangements in these “mesoscopic” species (see Figure ). Resulting from a symmetry-driven self-assembling process, the Keplerate-type structure exhibits a high idealized I h symmetry combining 12 archetypical pentagonal motifs {M­(M) 5 O 21 } with M = Mo or W, held together through 30 {Mo 2 E 2 O 2 } linkers with E = O , or S in a spheroidal topology. In addition to the tunable composition of the inorganic skeleton, the nature of the 30 inner ligands can be changed from acetate (for the most classical inner ligand) to specific ligands, thus giving the possibility of tuning the inner functionalities of the capsule, such as hydrophobicity/hydrophilicity, , charge density, or coordination properties. ,, Such chemical and structural features influence the transfer capacities of specific substrates across the 20 channels. This scenario has been nicely described by Müller and co-workers, who demonstrated that the active pores {Mo 9 O 9 L 3 }, where L = sulfate or phosphate, are able to trap specific cations in specific positions or recently that the large hydrophobic inner cavity is accessible for large organic guests and sequestration of hydrophobic molecules. Structural characterizations of mixed salts of {Mo 132 } revealed that well-defined sites located in the vicinity of the sulfate-type pores {Mo 9 O 9 (SO 4 ) 3 } coordinate specifically a variety of cations such as alkali (Na + , Rb + , and Cs + ) or organic (guadininium or protonated urea) cations …”
Section: Introductionmentioning
confidence: 99%
“…The Keplerate-type POMs belong to this class of compounds and correspond probably to one of the most fascinating and aesthetic arrangements in these “mesoscopic” species (see Figure ). Resulting from a symmetry-driven self-assembling process, the Keplerate-type structure exhibits a high idealized I h symmetry combining 12 archetypical pentagonal motifs {M­(M) 5 O 21 } with M = Mo or W, held together through 30 {Mo 2 E 2 O 2 } linkers with E = O , or S in a spheroidal topology. In addition to the tunable composition of the inorganic skeleton, the nature of the 30 inner ligands can be changed from acetate (for the most classical inner ligand) to specific ligands, thus giving the possibility of tuning the inner functionalities of the capsule, such as hydrophobicity/hydrophilicity, , charge density, or coordination properties. ,, Such chemical and structural features influence the transfer capacities of specific substrates across the 20 channels. This scenario has been nicely described by Müller and co-workers, who demonstrated that the active pores {Mo 9 O 9 L 3 }, where L = sulfate or phosphate, are able to trap specific cations in specific positions or recently that the large hydrophobic inner cavity is accessible for large organic guests and sequestration of hydrophobic molecules. Structural characterizations of mixed salts of {Mo 132 } revealed that well-defined sites located in the vicinity of the sulfate-type pores {Mo 9 O 9 (SO 4 ) 3 } coordinate specifically a variety of cations such as alkali (Na + , Rb + , and Cs + ) or organic (guadininium or protonated urea) cations …”
Section: Introductionmentioning
confidence: 99%
“…We report a new class of functional assemblies, wherein the hydrophobic effect 9,10 drives the spontaneous uptake of alkyl and alkylaromatic guests 11 by porous 200 nm diameter supraspheres whose host capacities are orders of magnitude larger than those of individual cages or containers. On a mass-per-volume basis, the level of uptake rivals those of zeolites and metal-organic frameworks, which, for methane at elevated pressures, reach values of 52 and 160 g l , respectively, for a crystalline aluminosilicate (zeolite) with 5 Å pores (100 bar, 293 K) 12 and the metal-organic framework, Fe(bdp), comprising Fe(II) and 1,4-benzenedipyrazolate linkages (70 bar, 298 K) 13 .…”
mentioning
confidence: 99%
“…26 In the past decade, porous polyoxometalate capsules consisting of 132 molybdenum atoms have been studied in the context of host−guest chemistry. 27,28 In addition, the guest cavities of these capsules have been used as "nanoreactors" showing very significant acceleration of acid catalyzed hydrolysis of ethers. 29,30 Here, we present the electrochemical cathodic oxygenation of light alkanes and alkenes, notably ethane to acetic acid at 1.8 V under aerobic conditions in water at room temperature using an iron−tungsten porous spherical capsule, {Fe III 30 W VI 72 } in shorthand, 31 as catalyst Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…36 In addition, previous research has shown that methane is a poorly incorporated guest into nearly isostructural {Mo 132 } capsules, relative to better incorporation of higher alkanes. 27 The lack of reactivity of methane could be associated with this phenomenon.…”
mentioning
confidence: 99%